Method for increasing local heat generation with nanometer material - CHENG ZHANG; GUOHUA SHI; HUA QIN (2004)
A method for using nano material to increase the local generation of heat includes such steps as preparing a specific target composition from the solution of a nano material, specific target agent and additive, injecting or embedding it to the particular position in an object, and acting it by endogenetic field, RF, magnetic field, or microwave to make its temp 1-30 deg.C, higher than peripheral temp in the object. Its advantages are high correctness and high effect. 本发明提供一种纳米材料能使局部产热增加的方法，其特征是该方法使用纳米材料的溶液与特异性靶向剂在固加剂的固加下形成纳米材料一特异性靶向复合体，而后对物体内特定部位进行注射或包埋，再在内生场、射频变、变磁场或微波作用下，特定部位的温度比周围的温度高1-30℃。本发明能在物体内定位加热、准确性高、升温明显，是一种有显著效益的先进加热方法，可广泛使用于工、农、医和制造行业。